The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/fsn3.2921
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐liposomal encapsulation of Artemisia aucheri phenolics as a potential phytobiotic against Campylobacter jejuni infection in mice

Abstract: Background Artemisia aucheri contains antibacterial phenolic compounds. The current work was implemented to evaluate the effectiveness of a nanoliposome‐encapsulated phenolic‐rich fraction (PRF‐NLs), as a dietary phytobiotic derived from Artemisia aucheri's areal parts, on the inhibition of enteropathogenic Campylobacter jejuni (C. jejuni) infection in mice. Methods The phenolic‐rich fraction was loaded into the nanoliposome structure to obtain a nanometer‐scale size liposome with homogenous dispersion. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Furthermore, Mohammed et al [ 58 ] reported on significant levels of hydroquinone and 4-hydroxybenzoic acid in A. inculta extracts demonstrating antibacterial activity. To the best of our knowledge, ellagic acid, a hydroxybenzoic acid dimer, has not been previously reported in A. inculta ; however, it was a main phenol in A. aucheri [ 59 ], while an ellagic acid derivative was detected in A. argentea L’ Hér alcoholic extract [ 40 ]. Ellagic acid is abundant in various fruits such as pomegranate, strawberry, raspberry and blackberry.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Mohammed et al [ 58 ] reported on significant levels of hydroquinone and 4-hydroxybenzoic acid in A. inculta extracts demonstrating antibacterial activity. To the best of our knowledge, ellagic acid, a hydroxybenzoic acid dimer, has not been previously reported in A. inculta ; however, it was a main phenol in A. aucheri [ 59 ], while an ellagic acid derivative was detected in A. argentea L’ Hér alcoholic extract [ 40 ]. Ellagic acid is abundant in various fruits such as pomegranate, strawberry, raspberry and blackberry.…”
Section: Resultsmentioning
confidence: 99%
“…The aerial parts of the M. longifolia L. were extracted based on a previously published method [18]. The essential oil was extracted using Soxhlet, as described earlier by Ghareh Bashlouei et al [19].…”
Section: Extraction Proceduresmentioning
confidence: 99%